Barbarisms in the language of radio and television spanish programs. - Maldonado, Dolores (2010)
One of the most important means of transmission of words and expressions is mass media. The language of the media shows a very wide lexicon which helps speaker enrich popular speech. But it might also happen that the lexicon listened to in these means can lead speakers to adopt poor or erroneous expressions, consequently linguistic vices, errors committed by broadcasters and television presenters in sport programs, news programs, live reports, and talk shows.In fact, society is in the habit of considering correct everything that comes from the language of mass media, but unfortunately it is not so, because they fall into the habit of not discussing the construction of informative speeches. The journalist has a social responsibility that goes beyond the maximum objectivity and impartiality of news, which is to use language correctly, because the media have power to influence the way we perceive events. A phrase that comes to summarize the influence of media on the useof language is "what has been said on TV".